Enhancing the shelf life and postharvest life quality of tomato (Solanum lycopersicum) - Olga B. Álvarez-Pérez; Cristian Torres-León; Janeth M. Ventura Sobrevilla; Romeo Rojas; Miguel A. Aguilar González; Raúl Rodríguez-Herrera; Cristóbal N. Aguilar (Exploration of Foods and Foodomics)
Aim: Worldwide, postharvest losses of tomato (Solanum lycopersicon cv. Roma) are around 50% due to physical and biological factors being this crop, one of the most important horticultural products with extensive fresh consumption. In this work, the effects of coatings of whey protein and candelilla wax with and without polyphenols from tarbush on the extension of the shelf life and postharvest quality of tomatoes were evaluated. Methods: An optimized suspension of protein-candelilla wax-glycerol (CC treatment) was applied as an edible coating to green mature tomatoes stored at room temperature (mature stage 2). The same suspension was supplemented with polyphenols from tarbush at 500 ppm (CP treatment). Tomato fruits without edible coating were used as a control treatment (SC). Various quality parameters were evaluated [color, weight loss, firmness, pH, titratable acidity and °brix (TSS)] and a sensory analysis was performed by a trained panel. Results: Tomatoes with the CC treatment showed the best shelf life extension results [color, weight loss, firmness, pH, titratable acidity, and °brix (TSS)] compared to the control and the polyphenol treatment, which showed the opposite result. In terms of sensory analysis, tomatoes with the CC treatment showed a better overall acceptability and appearance at the final time. Conclusions: Using CC treatment, the ripening process can be significantly delayed, and the postharvest life quality of tomatoes at room temperature in the breaker stage can be extended up to this time without any spoilage.